Implementing sidik gizi: A digital screening program for mapping nutritional status of adolescents in islamic boarding school - Fatati Larasati; Rifqy Rosyidah Ilmi; Alya Nabilah (International Journal on Health and Medical Sciences, 2026)
Traditional, paper-based health logging in residential schools often hinders timely public health responses due to manual diagnostic calculation lags. This study aimed to implement and evaluate "SIDIK GIZI" (Sistem Digital Skrining Gizi Mandiri), an e-Health application designed to streamline adolescent nutritional surveillance and assess end-user satisfaction. A cross-sectional implementation study was conducted in May 2026 at Pondok Salafy Al Fithroh, Gresik, Indonesia. Anthropometric data, comprising body weight, height, mid-upper arm circumference (MUAC), and waist circumference, were digitally registered from adolescent students (santri). Concurrently, system validation was measured using an integrated 5-point Likert scale survey completed by Santri Husada volunteers who operated the system across three domains: Ease of Use, Efficiency & Usability, and Usefulness & Impact. The application successfully mapped double-burden malnutrition indicators, flagging specific prevalence rates for underweight, stunting, chronic energy deficiency (CED) risks, and abdominal obesity. Furthermore, user satisfaction analysis demonstrated exceptionally positive feedback, specifically highlighting automated formula calculations, practical navigation layouts, and enhanced operational confidence among non-medical peer cadres. SIDIK GIZI reduced field screening times to 15–20 minutes per student while eliminating manual recording errors. In conclusion, this digital tracking model offers a sustainable, highly accepted health informatics framework that empowers boarding school communities to execute autonomous health monitoring, paving the way for data-driven preventive nutrition programs.